A Model to Overcome Critical Factors Involved in Project Outcome - Malhotra, Anamica (Digital Repository of Theses, 2024)
There are parallels between this world and even the simplest project. Humans are a relatively minor part of the universe. This vast universe is made up of numerous galaxies, and life dwell in one of them, known as the Milky Way. This Milky Way galaxy may contain a multitude of solar systems, with planet Earth having its own spot in one of them. In addition, while humans are a minor component of the earth, every minor component of the solar system has a job to play. Not a single entity, large or little, has been self-sufficient. The presence of one affects the other. Similarly, numerous elements regulate or govern how projects operate. When it is believed that any of the aspects is unimportant or try to disregard its impact on the project, that component plays its part that could really change the entire performance of the proposal. When a project starts, the aim is always to accomplish the final goal of that endeavour, and in order to do so, impact of all the aspects must be examined that can influence the project. The ultimate goal that is being discussed is, success. Success can mean different things to different people and have different definitions at different periods of life, yet the value of success remains constant. In this paper, first, several aspects that academics and researchers have investigated in the past are examined, and then critical evaluation is done, if the factors that have received all of the attention are important enough to overshadow other factors that have never been studied. What are the aspects that have never been discussed before but are extremely important will be the goal of this thesis work.